Arthropod microbiota: shaping pathogen establishment and enabling control - Pavanelo, Daniel B.; Piloto-Sardiñas, Elianne; Maitre, Apolline; Abuin-Denis, Lianet; Kopáček, Petr; Cabezas-Cruz, Alejandro; Fogaça, Andrea C. (Frontiers in Arachnid Science, 2023)
Vector–borne diseases (VBDs) pose significant global health threats. The microbiota of arthropod vectors influences their fitness and pathogen acquisition and/or transmission. Here, we review the intricate interplay among the arthropod immune system, the microbiota, and pathogens that limits or favors infection. We focused on the most important arthropod vectors, namely mosquitos, phlebotomines, tsetse flies, triatomines, and ticks, and expanded our analysis to include the nonvector model Drosophila melanogaster for comparison. The microbiota and immune system of arthropod vectors are targets for the development of promising control strategies, such as paratransgenesis and anti–microbiota vaccines. Further research should focus on elucidating the underlying mechanisms of vector–pathogen–microbiota interactions and optimizing anti–microbiota strategies. These approaches have the potential to combat VBDs and reduce their global impact.